The State as a Market Supervisor in Islamic Perspective - Muhammad Fathrul Quddus; Tika Widiastuti (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
Market participants can take various methods, ranging from acceptable practices to fraudulent methods. The State is expected to take on the role of the market supervisor so that both sellers and buyers can feel justice. The State has the right to regulate the course of the economy but with limits that are not detrimental to market players. In Islam, the market is controlled so that competition is carried out voluntarily. There must not be a party that is harmful to the party that is injured. This study aims to determine the role of the State as a market supervisor from an Islamic perspective. This study uses a descriptive method with a qualitative research approach. The data collection technique in this research is literature search from journals, books, electronic books, articles, and other information media related to the State's role in market supervision. The market supervisor in Islam is known as Al-Hisbah. The main task of al-hisbah is to invite the truth and forbid Munkar. In addition, Al Hisbah has three main functions, namely economic, social and moral functions. In contemporary times the position of al-hisbah can be a complementary role for a ministry or state agency.